PURE POLITICKING! RACIALISED BLAME GAMES AND MORAL PANIC IN THE CASE OF A SOUTH AFRICAN HIGH SCHOOL - CONRADIE, MARTHINUS STANDER (Society Register, 2020)
This study combines two discourse analytic frameworks, and explores the utility of this combination for unpacking journalistic opinions written in response to a polarising and racialised event in South African education: the Overvaal High School incident. It uncovers strategic constructions of racism within politicised blame games, in the context of Overvaal, and discloses how blame-assertion and blame-denial became implicated in framings of moral panic. Methodologically, this study relies on the concept race trouble, as well as a practical model of argumentation. In conjunction, these two approaches supply insight into both the calculated construction of racism, as well as the incorporation of these constructions into arguments aimed at rationalising blame-assertion and blame-denial. The results are interpreted within theorisations of moral panic. The findings showcase how arguments are produced to blame an individual politician for escalating racial antagonism around Overvaal, instead of offering a deeply historicised and contextualised account of the incident. Consequently, the arguments that shaped the opinion pieces, and the framing of racism involved in these arguments, ultimately obfuscate inquiry into structural determinants of racial inequity. Implicitly, this framing of racism and its incorporation into argumentation and blame games, produce a form of moral panic, in which South Africans racialised as white are construed as embattled by self-serving (black) politicians. Such politicians are vilified, or rendered as folk devils, and the results indicate how this process evades penetrating analyses of racialisation and its intersection with unequal education.